Analysis of Financial Behavior With Financial Technology as a Mediating Variable in Bulak Fish Centers Surabaya and Surrounding Areas - Shinta Anugrah Dyani; Rahman Amrullah Suwaidi (Jurnal Ekonomi, 2025)
This study aims to analyze the influence of financial literacy, locus of control, and lifestyle on financial behavior through financial technology in the community in the Bulak Fish Center area, East Surabaya. The method used in this study is a survey with a questionnaire distribution to 100 respondents who are local residents. Based on the results of data analysis and previous discussions, the following conclusions can be drawn: Financial literacy can contribute to the financial behavior of the community in the Bulak Fish Center area in East Surabaya; Locus of control can contribute to the financial behavior of the community in the Bulak Fish Center area in East Surabaya; Lifestyle can contribute to the financial behavior of the community in the Bulak Fish Center area in East Surabaya; Financial literacy can contribute to financial behavior through financial technology of the community in the Bulak Fish Center area in East Surabaya; Locus of control can contribute to financial behavior through financial technology of the community in the Bulak Fish Center area in East Surabaya; and Lifestyle can contribute to financial behavior through financial technology of the community in the Bulak Fish Center area in East Surabaya.